Community-based ecotourism management for sustainable development of marine protected areas in Malaysia. (February 2017) - Masud, Muhammad Mehedi; Aldakhil, Abdullah Mohammed; Nassani, Abdelmohsen A.; Azam, Mohammad Nurul
Abstract: This study explores the factors that influence the community's participation in managing community-based ecotourism (CBETM) for sustainable development of Marine Protected Areas (MPAs) in Peninsular Malaysia. CBETM ensures community involvement for effective sustainable management as well as supporting environmental conservation practices. To achieve the objectives of the study, a quantitative method was applied, and data were analysed using structural equation modelling (SEM). The major findings of this study indicate that environmental knowledge for sustainable development, motivation to be involved with CBETM, perceived economic impact of CBETM, perceived social impact of CBETM and perceived cultural impact of CBETM have a greater influence on intention to participate in CBETM. It implies that these factors lead to the formation of positive intention in managing CBETM and promote community participation. This study will help policymakers to take relevant management policies to increase environmental knowledge for sustainable development, to motivate local community in CBETM, and to increase economic, social and cultural benefits among residents. These benefits encourage community involvement in CBETM that will support environmental planning to ensure environmental conservation practices among tourists and residents. Highlights: The study evaluates the economic, social and cultural impact of CBETM. CBETM supports environmental planning to ensure conservation practices within MPAs. The study suggests to take proper policies for sustainable development of CBETM.